The donor of carbon monoxide (CORM-2) affects the level of serum immunoglobulins and the state of the bone marrow during the immune response in mice - S. P. Beschasnyi; O. M. Hasiuk (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Toxic carbon monoxide in small concentrations has pro-apoptotic, anti-allergic, vasodilator effects, and stimulates angiogenesis. The problem with the therapeutic use of low doses of carbon monoxide is that it is difficult to dose. To control the amount and gradual release of carbon monoxide, non-toxic preparation is used - CO donor based on carbonyl compound of ruthenium (CORM-2).